Does COVID-19 Pandemic Transform the Performance Management of North Indralaya Sub-district Government? - Faisal Nomaini; Sofyan Effendi; Oemar Madri Bafadhal; Anang Dwi Santoso (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTThe purpose of this study is to illustrate how sub-district governments manage performance during a time of crisis, specifically the COVID-19 pandemic. When the pandemic struck, the government, which had been criticized for its excessive concentration on routine and administrative affairs, was at a loss for how to respond. COVID-19 requires the government to perform double duty since it must continue to deliver ordinary public services while also working harder to contain the spread of COVID-19 at all levels. Thus, performance management is critical for assuring organizational performance and managing the performance of its personnel in the face of increasing work stress and work-related weariness. This study employed a qualitative method and a case study approach in the North Indralaya sub-district government. The study’s findings indicate that, aside from implementing work- from-home policies and increasing the use of information and communication technologies in public services, the sub-district government has made few modifications to performance management. As a practical consequence, adaptive and evidence-based performance management must be implemented to enable a more rapid response to the dynamics of society as a result of the COVID-19 pandemic. Due to the qualitative nature of the current study, a future study may examine the same issue using quantitative research, assessing the influence of current performance management on employee satisfaction, performance, and motivation. Keywords: Performance management, sub-districts, Covid-19 ABSTRAKTujuan dari penelitian ini adalah untuk mengkaji bagaimana pemerintah kecamatan mengelola kinerja pada masa krisis, khususnya pandemi COVID-19. Ketika pandemi melanda, pemerintah yang dikritik karena konsentrasinya yang berlebihan pada urusan rutin dan administrasi, memiliki sedikitpengetahuan tentang bagaimana meresponsnya. COVID-19 menuntut pemerintah untuk melakukan tugas ganda, karena harus terus memberikan pelayanan publik biasa sambil juga bekerja lebih keras untuk menahan penyebaran COVID-19 di semua tingkatan. Dengan demikian, manajemen kinerja sangat penting untuk memastikan kinerja organisasi dan mengelola kinerja personelnya dalam menghadapi peningkatan stres kerja dan kelelahan terkait pekerjaan. Penelitian ini menggunakan metode kualitatif dan pendekatan studi kasus di Pemerintah Kecamatan Indralaya Utara. Temuan studi menunjukkan bahwa, selain menerapkan kebijakan bekerja dari rumah dan meningkatkan penggunaan teknologi informasi dan komunikasi dalam layanan publik, pemerintah kecamatan hanya melakukan sedikit modifikasi pada manajemen kinerja. Sebagai konsekuensi praktis, manajemen kinerja yang adaptif dan berbasis bukti harus diterapkan untuk memungkinkan respons yang lebih cepat terhadap dinamika masyarakat akibat epidemi COVID-19. Karena sifat kualitatif dari studi saat ini, studi masa depan dapat memeriksa masalah yang sama menggunakan penelitian kuantitatif, menilai pengaruh manajemen kinerja saat ini terhadap kepuasan, kinerja, dan motivasi karyawan.Kata Kunci: Manajemen kinerja, kecamatan, Covid-19